The use of cues for attention in ancient Greek art: aspects that influence concentration in the work of art and its elements - Duarte, Antonio M.; Stefanakis, Manolis I. (Arte, Individuo y Sociedad, 2015)
The goal of this study is to identify cues for the cognitive process of attention in ancient Greek art, aiming to find confirmation of its possible use by ancient Greek audiences and artists. Evidence of cues that trigger attention’s psychological dispositions was searched through content analysis of image reproductions of ancient Greek sculpture and fine vase painting from the archaic to the Hellenistic period - ca. 7th -1st cent. BC. Through this analysis, it was possible to observe the presence of cues that trigger orientation to the work of art (i.e. amplification, contrast, emotional salience, simplification, symmetry), of a cue that triggers a disseminate attention to the parts of the work (i.e. distribution of elements) and of cues that activate selective attention to specific elements in the work of art (i.e. contrast of elements, salient color, central positioning of elements, composition regarding the flow of elements and significant objects). Results support the universality of those dispositions, probably connected with basic competencies that are hard-wired in the nervous system and in the cognitive processes.